Pelaksanaan Bimbingan Belajar oleh Orang Tua dalam Perkembangan Moral Spiritual Anak di Raudhatul Athfal - Siti Habsoh; Endin Nasrudin; Adi Rosadi (Institut Madani Nusantara, 2021)
Guidance by parents can be interpreted as a help given by parents to a child in order to develop the potential (talents, interests, and abilities) that have, recognize themselves, overcome problems so that the child can determine his own way of life responsibly without relying on others. The results of this study found. 1) Some parents who are apathetic in doing guidance in learning in the moral development of the child spritual, on the grounds of busy housework, but there are also parents who do tutoring to their children. 2) Parents who do guidance to their children have done the maximum there are only a few things that must be considered in doing guidance to the child. 3) The supporting factor is that there is still awareness from parents to always educate and guide their children in their learning activities and there is a family atmosphere full of affection so that it creates a comfortable atmosphere for children in their learning. While the inhibition factor is entertainment from technology such as hand phones and tv, which interferes with children's learning guidance activities. As well as the influence of the surrounding environment that can cause the child to prefer to play rather than learn. 4) There are differences between children who are guided by parents and are not guided by parents in the moral development of children in school, children who are guided to learn by their parents are more obedient and subject to different school rules than children who are not guided by parents.